Analysis of clinical anatomical correlates of motor deficits in stroke by multivariate lesion inference based on game theory - Toba, Monica N.; Malherbe, Caroline; Zavaglia, Melissa; Arnoux, Audrey; Barbay, Mélanie; Hilgetag, Claus C.; Godefroy, Olivier (Frontiers in Neuroscience, 2025)
IntroductionThe exploration of causal functional inferences on the basis of deficits observed after neurological impairments is often based on the separate study of gray matter regions or white matter tracts. Here, we aimed at jointly analysing contributions of gray matter and white matter by using the domain of motor function and the approach of iterative estimated Multi-perturbation Shapley Analysis (MSA), a multivariate game-theoretical lesion inference method.MethodsWe analyzed motor scores assessed by the National Institute of Health Stroke Scale (NIHSS) together with corresponding lesion patterns of 272 stroke patients using a finely parcellated map of 150 gray matter regions and white matter tracts of the brain.ResultsMSA revealed a small set of essential causal contributions to motor function from the internal capsule, the cortico-spinal tract, and the cortico-ponto-cerebellum tract.DiscussionThese findings emphasize the connectional anatomy of motor function and, on the methodological side, confirm that the advanced multivariate method of iterative estimated MSA provides a practical strategy for the characterization of brain functions on the basis of finely resolved maps of the brain.